A atualidade do pensamento de Paulo Freire na educação de jovens e adultos no século XXI - Lemos, Silvana Donadio Vilela (2010)
The goal of this research was to verify how up-to-date and important Paulo Freire´s thinking is for the Education of Youth and Adults and for the development of research went to the premises of qualitative research. The methodological procedures were used to search text of authors of today located in libraries and educational sites, analysis of dissertations and theses in the Brazilian Portal of Scientific Information, interviews with renomed researchers of Brazil, Latin America and Europe and with educators of Youth and Adults. The meetings in Paulo Freire`s Catedra in The Catholic University of São Paulo, open space for dialogue and reflection critical analysis of the work of dissertations and theses, provide a unique opportunity to build and develop this research. The criteria for selection of respondents, where interviewers were based on the value of the bibliographic on the themes Popular and Youth and Adults Education in Latin America, Europe and Brazil as well as the engagement of professionals in the fight for a liberating education. In the case of teachers, was taken into account as a criterion, the practical significant of these educators as literacy. Given these criteria were selected eleven professionals. Among the Paulo Freire`s major categories highlighted by the authors researched which confirm how up-to-date and important Paulo Freire s thoughts stood out: the unity of theory and practice, the politics of education, the knowledge gained from experience, awareness, reading the dialog and the world in the process of literacy. It follows the end of this study, Paulo Freire`s thought in the XXI century, remains a significant theoretical framework for the literacy of Youth and Adults, to propose a job outside the field of reading skills and writing. The proposed literacy Paulo Freire is still recognized and practiced as a call to life, which challenges the subject to a critical understanding of transformation toward a more just, democratic and solidarity